Mejoramiento de procesos constructivos en muros de la Empresa Constructora Volio y Trejos - Mena-Zúñiga, Bryan (Instituto Tecnológico de Costa Rica, 2017)
Measuring how much production is obtained when constructing is an issue that has been increasing little by little along with construction companies because they seek to optimize expenses and increase profit every day. The construction industry is growing in Costa Rica, giving as a result, that national companies get interested in knowing how effective their construction processes are performed. This project seeks to improve those processes in Volio and Trejos Asociados construction company by studying and sampling the formwork of reinforced concrete elements. Thus, ten different samples were done in towel U Nunciatura project, using methods like Crew balance, Work sampling, and Five minutes rating to establish both the quantitative and the qualitative values. Moreover, tools like Ishikawa diagram, Labor surveys, Flow diagram, and Travel diagram were applied to determine the low production reasons. As a result, fatigue, tiredness, time lost due to laziness, delays when beginning the formwork due to lack of previous land leveling, broken tools and few working units that create the necessity of waiting for available ones, moreover; the lack of a good work plan for the tower crane, and storing construction materials far away from work zone, lack of space and/or too much populated work zones, high temperatures, and not enough water dispensers are the most important conclusions mentioned in this project.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Productividad; Diagramas; Construcción; Optimización; Costos